TANGGUNG JAWAB NOTARIS TERHADAP PINJAM NAMA ANTARA DEBITUR DENGAN BANK TERKAIT KREDIT PERUMAHAN RAKYAT SUBSIDI - Karina Putri Marina (Fakultas Hukum Universitas Trisakti, 2022)
Subsidized home ownership credit in Indonesia cannot be borrowed from other parties. This is because Borrowing a Name on Subsidized Home Ownership Credit waives the requirements so that anyone can get Subsidized Home Ownership Credit. Homeownership credit can generally be divided into two categories: home ownership credit and subsidized home ownership credit. The basic difference is the classification of people who are intended to receive the credit program. As is known, subsidized home ownership credit is a credit facility provided to lower-middle-class people. In practice, many middle- and lower-class people have a bad track record regarding credit and are therefore refused to apply for subsidized home ownership credit; therefore, these parties use the names of people they know to be able to get the house. Borrowing names related to subsidized home ownership credit is not only misused by the lower middle class but also abused by the upper middle class for their interests, namely for investment or for their ownership. To obtain subsidized home ownership credit, a person must go through Bank Indonesia Checking, a credit history check in the Bank Indonesia Debtor Information System.